PENGARUH MOTIVASI, KEPUASAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA PT. KURNIA JAYA BERSAMA) - Hardi Pratama; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this research to determine the influence of Work Motivation, Job Satisfaction and Work Environment towards Employee Performance of the PT Kurnia Jaya Bersama. The data used in this study is primary data. The population used is employees of PT Kurnia Jaya Bersama. The sampling technique was done by saturated sampling method. The sample of this research is 73 employees. Data analysis was done by using multiple linier regression method. The result of this study indicate that Simultaneously, Motivation, Job Satisfaction and Work Environment significantly affected the Employee Performance. Partially, motivation has a positive significant effect on employee performance, job satisfaction has a negative significant on employee performance and work environment has a positive significant on employee performance.  Keywords : Work Motivation, Job Satisfaction, Work Environment, Employee Performance